2014
DOI: 10.1007/s10972-014-9392-1
|View full text |Cite
|
Sign up to set email alerts
|

Equitable Written Assessments for English Language Learners: How Scaffolding Helps

Abstract: This study investigated the effects of the use of scaffolds in written classroom assessments through the voices of both native English speakers and English language learners from two middle schools. Students responded to assessment tasks in writing, by speaking aloud using think aloud protocols, and by reflecting in a post-assessment interview. The classroom assessment tasks were designed to engage students in scientific sense making and multifaceted language use, as recommended by the Next Generation Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…• Making connections between the parts of the item to provide contextual support • Adding a brief narrative to elicit understanding of how the concept being assessed is applied in a real-world scenario The EFCA has been used to reduce the linguistic complexity of life sciences assessment items without reducing the items' level of content difficulty. 8,9 These studies showed promising results in decreasing the performance gap between ELL and NES students. The EFCA guidelines were applied to modify life science assessment items for middle school students in a pre-test/post-test design.…”
Section: Addition Of Storylinementioning
confidence: 97%
See 2 more Smart Citations
“…• Making connections between the parts of the item to provide contextual support • Adding a brief narrative to elicit understanding of how the concept being assessed is applied in a real-world scenario The EFCA has been used to reduce the linguistic complexity of life sciences assessment items without reducing the items' level of content difficulty. 8,9 These studies showed promising results in decreasing the performance gap between ELL and NES students. The EFCA guidelines were applied to modify life science assessment items for middle school students in a pre-test/post-test design.…”
Section: Addition Of Storylinementioning
confidence: 97%
“…8 To gain a deeper understanding of students' interpretations of original versus modified assessment items, researchers conducted a qualitative study involving ELL and NES middle school students. 9 Items were selected from a pool of questions outlined in the life sciences curriculum ("original versions"). The EFCA guidelines were then used to create linguistically simplified and visually accessible versions of each of the original assessment items ("modified versions").…”
Section: Addition Of Storylinementioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' understandings and beliefs of EA are important because they shape teachers' instructional and assessment practices to meet the needs of diverse learners (Abell & Siegel, 2011;Siegel, 2014;Siegel et al, 2014). EA is not just a way to measure students' learning fairly, but more importantly, it is a way to reduce biases to support all students' learning (Siegel, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…After the recognition of the importance of formative assessment researchers began focusing on other aspects of formative assessment (e.g., Fusco & Calabrese Barton, 2001). Researchers generally focus on the English Language Learner's [ELL] needs (Lyon, Bunch, & Shaw, 2012;Siegel et al, 2014;Siegel, Wissehr, & Halverson, 2008); assessment sensitivity to cultural differences (e.g., Solano-Flores & Nelson-Barber, 2001); student and teacher interaction (e.g., ; sharing authority (e.g., Fusco & Calabrese Barton, 2001); and identity development (e.g., Fusco & Calabrese Barton, 2001).…”
Section: Figure 21 Aspects Of Formative Assessmentmentioning
confidence: 99%